3D Printing and Bio-Based Materials in Global Health : An Interventional Approach to the Global Burden of Surgical Disease in Low-and Middle-Income Countries - Bhatia, Sujata K.; Ramadurai, Krish W. (Springer International Publishing : Imprint: Springer, 2017)
This book examines the potential to deploy low-cost, three-dimensional printers known as RepRaps in developing countries to fabricate surgical instruments and medical supplies to combat the "global surgical burden of disease." Approximately two billion people in developing countries around the world lack access to essential surgical services, resulting in the avoidable deaths of millions of individuals each year. A fundamental barrier that inhibits access to surgical care in these locations is the lack of basic surgical instruments and supplies in healthcare facilities. RepRap printers are highly versatile 3D printers assembled from basic, domestically sourced materials that can fabricate low-cost surgical instruments on-site, ultimately enhancing the interventional capacity of healthcare facilities to treat patients. Rather than focusing on one specific field of interest, this book takes an integrative approach that incorporates topics and methods from multiple disciplines ranging from global health and development economics to materials science and applied engineering. These topics include the feasibility of using bio-based plastics to fabricate surgical instruments via 3D printing sustainably, the application of "frugal innovation and engineering" in resource-poor settings, and analyses related to the social returns on investment, barriers to entry, and current and future medical device supply-chain paradigms. In taking a multi-disciplinary approach, the reader can gain a holistic understanding of the multiple facets related to implementing medical device innovations in developing countries.
Keywords: Materials science.; Health care management.; Health services administration.; Biomedical engineering.; Public health.; Biomaterials.; elektronické knihy; electronic books